ANALISIS KEPUASAN MAHASISWA TERHADAP SISTEM PEMBELAJARAN ONLINE PADA MASA PANDEMIC COVID 19 DI STMIK AKAKOM DENGAN METODE NAIVE BAYES - Sur Yanti; Danny Kriestanto (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2022)
In accordance with the circular of the Minister of Education and Culture of the Republic of Indonesia regarding Circular Letter Number 4 of 2020 concerning the Implementation of Educational Policies in the Emergency Period for the Spread of Corona Virus Disease (COVID-19), the learning system implemented is online. STMIK AKAKOM is one of the universities that has also implemented online lectures since the government's policy for the home learning system was established. Various efforts have been made by STMIK AKAKOM to carry out the online learning process during this covid-19 pandemic. Therefore, researchers conducted a study that aims to analyze the success of the online learning system for students conducted at STMIK AKAKOM with the Naive Bayes method approach, using 4 (four) criteria, namely Communication, Building a Learning Atmosphere, Assessment of Students, and Delivery of Lecture Materials. The level of satisfaction assessment using a Likert scale (likert scale) 5 points with the same interval. starting from point 1 (one) which states very less, to point 5 (five) which states very well. Based on the results of calculations that have been carried out, it can be seen that the classification of testing data from respondents numbered R89 to R93 for online learning systems during the Covid 19 pandemic is satisfied.